A Guide to Impact Fees and Housing Affordability - Arthur C. Nelson (Island Press, 2008)
A Guide to Impact Fees and Housing Affordability demonstrates for practitioners exactly how a fair impact-fee program can be designed and implemented. In addition, it includes information on the history of impact fees and discusses alternatives to them, summarizes state legislation that can influence the design of local fee programs, and provides case studies with useful illustrations of successful programs.